SR-B1-targeted nanodelivery of anti-cancer agents: a promising new approach to treat triple-negative breast cancer - Johnson R (Dove Medical Press, 2017)
Rebecca Johnson,1 Nirupama Sabnis,2 Xiangle Sun,1 Ruhani Ahluwalia,3 Andras G Lacko2,4 1Institute of Molecular Medicine, 2Institute for Cardiovascular and Metabolic Diseases, University of North Texas Health Science Center, 3Harmony School of Innovation, 4Department of Pediatrics, University of North Texas Health Science Center, Fort Worth, TX, USA Abstract: Patients with triple-negative breast cancer (TNBC) have a considerably less favorable prognosis than those with hormone-positive breast cancers. TNBC patients do not respond to current endocrine treatment and have a 5-year survival prognosis of <30%. The research presented here is intended to fill a void toward the much needed development of improved treatment strategies for metastatic TNBC. The overall goal of this research was to evaluate the effectiveness of reconstituted high-density lipoprotein (rHDL) nanoparticles (NPs) as delivery agents for anti-TNBC drugs. Using lapatinib and valrubicin as components of the rHDL/drug complexes resulted in a significantly better performance of the NP-transported drugs compared with their free (unencapsulated) counterparts. The enhancement of the therapeutic effect and the protection of normal cells (cardiomyocytes) achieved via the rHDL NPs were likely due to the overexpression of the high-density lipoprotein (HDL) (scavenger receptor class B type 1 [SR-B1]) receptor by the TNBC cells. Keywords: breast cancer, TNBC, rHDL nanoparticles, SR-B1 receptors, targeted drug delivery, lapatinib, valrubicin